THE INFLUENCE OF ACCOUNTANCY ERRORS ON FINANCIAL AND TAX REPORTS - Mariana GURĂU; Maria Zenovia GRIGORE (Challenges of the Knowledge Society)
To make mistakes is human. An accountant may do mistakes, too. Accountancy errors are defined and classsified by accounting regulations. These set what is the accountant treatment for correcting accountancy errors. However, even though one of the objectives in accounting normalization is made by the disconnection between accountancy and taxation, the accountancy errors influence especially tax reports. We will further point the impact of accountancy errors on financial and tax reports. We will also approach the accountancy principles that impose the rules described for correcting the errors.